2002
DOI: 10.1111/j.1530-0277.2002.tb02632.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Light to Moderate Alcohol Consumption and Risk of Hypertension in Japanese Male Office Workers

Abstract: Light to moderate alcohol consumption seems to have an important influence on BP in both young and middle-aged Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Two studies53, 55 were judged to be of serious risk of bias, 1 of low risk, and 16 of moderate risk of bias mainly because of the observational study design and 1‐time measurement of alcohol consumption (Table S2). Thirteen studies used clinical measurements of BP to determine incidence of hypertension 22, 23, 24, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57. Similar relationships were found when we excluded studies with potential serious risk of bias and that relied on self‐reported incidence of hypertension (Figures S4 and S5).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Two studies53, 55 were judged to be of serious risk of bias, 1 of low risk, and 16 of moderate risk of bias mainly because of the observational study design and 1‐time measurement of alcohol consumption (Table S2). Thirteen studies used clinical measurements of BP to determine incidence of hypertension 22, 23, 24, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57. Similar relationships were found when we excluded studies with potential serious risk of bias and that relied on self‐reported incidence of hypertension (Figures S4 and S5).…”
Section: Resultssupporting
confidence: 52%
“…However, the number of incident hypertension cases was low and CIs were wide, indicating low statistical power to detect significant differences. Three studies presented results by age groups 46, 49, 51. There was no difference in incidence of hypertension by age group (per linear increase in 4 age categories; men: RR=0.95; 95% CI, 0.84–1.09; P =0.43; women: RR=0.99; 95% CI, 0.86–1.13; P =0.83); however, statistical power was also low.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Subjects for this study were 5218 Japanese men aged 23–59 years who participated in annual health examinations at A Corporation, one of the biggest building contractors in Japan, in 1996. Details of the study design and population characteristics are available in earlier reports [33, 34]. Briefly, all the participants were white‐collar workers and most have professional occupations.…”
Section: Methodsmentioning
confidence: 99%
“…Features of MS—obesity, high blood pressure, hypertriglyceridemia, low concentration of high‐density lipoprotein (HDL)‐cholesterol, and hyperglycemia—are established risk factors for cardiovascular disease and diabetes. The relation of alcohol consumption to these features is complex: although alcohol consumption has been associated with increased risk of hypertension (3), moderate alcohol consumption is associated with a lower risk of diabetes mellitus (4, 5, 6), perhaps through improved insulin sensitivity (7, 8). In addition, alcohol consumption is associated with higher HDL‐cholesterol (9, 10, 11) and higher triglycerides (TGs) (12).…”
Section: Introductionmentioning
confidence: 99%